When pulmonary embolism is not an obvious diagnosis - pathophysiology, risk factors, diagnosis, treatment and a review of the most unusual cases - Julia Kozakiewicz; Aleksandra Okońska; Kamil Kościelecki; Agnieszka Kalisz; Klaudia Mączewska; Iwona Skorulska; Patrycja Długozima; Aleksandra Głowacka; Weronika Grywińska; Paulina Grzeszczuk (Quality in Sport)
Introduction: This review paper aims to emphasize how pulmonary embolism is a seriously life-threatening disease entity, point out risk factors, symptoms, diagnostic trails, treatment and prove that a diagnosis, specifically aimed at embolism is often not obvious in given clinical cases.